Leadership distribué, leadership partagé : coopération et pouvoir - Serge Le Bihan (Recherches en Éducation)
In France, a lot of research has documented the role of “principals” in the secondary school. Within the framework of a study carried out in LACES (EA 4140), the author investigates the mechanisms of teamwork in six primary schools through questionnaires and the individual interviews with the headmasters. The theoretical model was the distributed leadership (Spillane, Halverson, Diamond, 2008). This study shows that for those tasks which imply people outside the school, the headmaster is the interface and that he can enforce actual distributed leadership. For the more pedagogical tasks, the leadership seems less obvious. Finally relational aspects and the attitudes to authority between the headmasters and the teachers are present in the exercise of the leadership.